2011
DOI: 10.1177/0333102411431333
|View full text |Cite
|
Sign up to set email alerts
|

Headache and prolonged dilatation of the middle meningeal artery by PACAP38 in healthy volunteers

Abstract: PACAP38-induced headache is associated with prolonged dilatation of the MMA but not of the MCA. Sumatriptan relieves headache in parallel with contraction of the MMA but not of the MCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 25 publications
11
156
0
Order By: Relevance
“…Nevertheless, more studies are necessary to further reveal the vasomotor effects of PACAP in various age groups. It is important to elucidate whether it has protective or deleterious effects, since previous studies assigned clinical significance for PACAP in headache due to prolonged dilation of cerebral arteries to PACAP (Amin et al 2012 ). In contrast, other studies demonstrated increased vascular contractile activity in older age (Ivic et al 2012 ), when relaxations to PACAP was less affected.…”
Section: Potential Roles Of Pacap1-38 Signaling Eliciting Relaxation mentioning
confidence: 99%
“…Nevertheless, more studies are necessary to further reveal the vasomotor effects of PACAP in various age groups. It is important to elucidate whether it has protective or deleterious effects, since previous studies assigned clinical significance for PACAP in headache due to prolonged dilation of cerebral arteries to PACAP (Amin et al 2012 ). In contrast, other studies demonstrated increased vascular contractile activity in older age (Ivic et al 2012 ), when relaxations to PACAP was less affected.…”
Section: Potential Roles Of Pacap1-38 Signaling Eliciting Relaxation mentioning
confidence: 99%
“…Our results draw attention to a possible influence between the PACAP and CGRP systems in migraine pathogenesis [125,220,221]. In addition there are evidence that PACAP shares expression and regulation simultaneous with CGRP [27,155,222].…”
Section: Possible Relations Between the Pacap-38 And Cgrp In Migraineurssupporting
confidence: 52%
“…• An MRI angiographic study has revealed that PACAP-38 infusion-induced headache is related to significant dilatation of middle meningeal arteries (MMAs), in contrast with middle cerebral arteries [155]. A PAC1 receptor antagonist can influence the vasodilating action of PACAP-38 on pressurized MMAs.…”
Section: Vascular Effects Of Pacap-38 Related To Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…This group has in addition reported that PACAP-38 results in a related increase in the diameter of cranial arteries (2,3). They propose that PACAP-38 caused vasodilation, which resulted in the headache, providing support for the vascular theory of migraine (4).…”
mentioning
confidence: 91%